NIMG-73. NEUROLOGICAL ASSESSMENT IN NEURO-ONCOLOGY (NANO) CORRELATES WITH INTEGRATED PREDICTIVE RADIOGRAPHIC BIOMARKERS OF PROGRESSED HIGH GRADE ASTROCYTIC TUMORS (IPROMPT): A PROPOSED SUPPLEMENT TO RANO. (11th November 2019) - Tosha Gatson, Na; Bross, Shane; Lockard, Laura; Leese, Erika; Manikowski, Jesse; Mahadevan, Anand; Conger, , Andrew; Mongelluzzo, Gino
Abstract: This year nearly 86, 000 persons in the US will be diagnosed with a primary brain tumor. Glioblastoma (GBM) is the deadliest and most common of these tumors in adults with overall survival around 15mos. Disease progression is inevitable, and effective second-line therapies are few. Delays in identifying progressed GBM risks neurologic decline, continuation of ineffective therapies, and increased tumor-mutational-burden, potentially rendering treatment less-effective. Brain tumor imaging can be ambiguous and is an active topic in neuro-oncology as there are currently no validated approaches to assessment of tumor treatment response. We present a single institution database including 622 gross-totally-resected GBMs (2006–2018) to evaluate changes in T2/FLAIR signal intensity (T2FSI), diffusion restriction, and contrast enhancement both in and around the resection cavity (RC) to determine earliest indicators of tumor progression. Analysis of NANO score was completed to correlate with predicted tumor progression. This is an early data release of an ongoing two-phased retrospective/prospective study with findings that support a novel integration of radiographic sequences and NANO to supplement established RANO criteria in earlier detection of GBM progression. Of 622 confirmed GBMs, 158 fit the rigorous criteria – included here are 58 cases. We report 70% (n=41) of patients show RC T2FSI correlating with restricted diffusion and increasing NANO score (0.5–1.4) as early as 3.8mos prior to and at time of radiographic progression, respectively. Previous studies have reported similar T2FSI but without associated NANO, less rigid inclusion criteria, and limited MRI sequences. We also report imaging phenomena, not previously described, such as FLAIR migration and FLAIR coring timed closely with progression . The proposed technique uses routine MRI, therefore readily standardized in clinical practice. With further validation, this novel integration of imaging and neurologic assessment might serve to supplement existing response criteria in GBM and improve clinician confidence in earlier detection of progression.